A Study on Individual Awareness and Perception Towards Blockchain Technology in India - Ravichandra, Thangjam; Madaan, Vandana; Sharma, Anil; Deshmukh, Sachin; Agrawal, Raju; Gumber, Gunjan; Khan, Mohammad Ahmar (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Blockchain is a decentralised database that records every transaction and digital occurrence. The parties who maintain the blockchain blocks share ownership of these transaction records, which are exchanged between parties and recorded in blocks. The parties who make up the network/system examine, confirm, and store each Block. Each block includes the specifics of a single transaction as well as the hash key from the preceding block. Blockchain serves as the foundation for Bitcoin and other forms of digital currency. Blockchains are very secure by design, and the technology guarantees error-free record keeping. Bitcoin is a decentralized digital money that is used for peer-to-peer transactions. In the Indian banking industry, electronic payments have achieved a significant breakthrough. They also continue to develop as fresh innovations are introduced to the current system. Paper-based transactions are gradually being replaced with electronic payments, saving time and money. More transparency has led to a rise in transaction volume, and the industry is showing good growth. The financial and banking industries have undergone a paradigm shift as a result of the entry of Bitcoin and other cryptocurrencies into these industries. Blockchain secures fundamental aspects of ownership, trust, and commerce and performs a disruptive intervention on the entire transaction management system. Exploring this technology constructively and critically in the context of India would open up new perspectives on how it should be used. This paper will summarise the present level of blockchain adoption in India in addition to highlighting the opportunities and challenges in this field.